Legal Accountability of Persons with Disabilities as Perpetrators of Criminal Acts of Sexual Violence - Isnaini, Enik; Kasumawati, Devi; Rupawanti, Nadia (Universitas Islam Lamongan, 2025)
In the Crime of Sexual Violence, a person with a disability is not only a potential victim, but can also be a perpetrator. People with disabilities are also categorized as legal subjects. This raises legal issues related to the capacity to be criminally responsible, as well as how the legal system provides fair treatment for both victims and perpetrators. However, it still provides fulfillment of rights and protection for people with disabilities as perpetrators of sexual violence. Legal accountability for people with disabilities as perpetrators of sexual violence must continue to be enforced in accordance with applicable regulations and perpetrators are required to be held accountable for their actions, if they are in a condition capable of being responsible. Therefore, in this case, it is not only providing justice for the victim but also for the perpetrator by paying attention to the law running fairly and non-discriminatory.